The Nauvari Saree - Mumbai Archive Project Team (Jio Institute, 2024)
The Nauvari saree, also known as the Kashta saree, is a traditional Maharashtrian attire worn by Koli women. The Nauvari saree is a nine-yard saree, as opposed to the regular six-yard saree. It is draped in a specific manner that allows for greater freedom of movement, making it practical for women engaged in the fishing business.